Are former heavy drinkers in the UK less likely to identify as being in recovery compared to those in the USA? A pilot test - John A Cunningham; Alexandra Godinho (BMC, 2021)
Abstract Background To provide a preliminary test of the prediction that fewer former heavy drinkers will identify themselves as being in recovery in the UK versus the USA. Methods An online cross-sectional survey was completed by a convenience sample of former heavy drinkers. This sample was identified from participants recruited to complete a questionnaire about alcohol consumption. The recruitment advertisement specified that the participants did not need to drink alcohol. The survey included items assessing self-reported current and past levels of alcohol consumption, alcohol dependence at time of heaviest alcohol consumption (ICD-10 criteria), and questions regarding identifying as currently or ever being in recovery taken from a survey by Kelly et al. (2018). Results Out of 5002 participants who completed the questionnaire, 150 were identified as former heavy drinkers from the UK or the USA. The proportion of participants reporting alcohol dependence, and the proportion of participants reporting past year abstinence, did not differ significantly between the UK and the USA (p = .841 and 0.300 respectively). Compared to participants from the UK, participants in the USA were more likely to report that they had a problem with drinking but now no longer do (24.1 % vs. 56.0 %; p < .001), and that they currently identified (4.2 % vs. 21.2 %; p = .003) or ever identified (7.4 % vs. 30.2 %; p = .001) as being in recovery. Conclusions Identifying as being in recovery appears more common in the USA than the UK among former heavy drinkers. This apparent difference in prevalence may reflect historic differences in treatment services offered in these countries, particularly with respect to the predominance of a 12-step approach in the USA. These findings should be replicated in a representative sample.